Prognostic value of undetectable hs troponin T in suspected acute coronary syndrome - Vafaie, Mehrshad; Slagman, Anna; Möckel, Martin; Hamm, Christian; Huber, Kurt; Müller, Christian; Vollert, Jörn O.; Blankenberg, Stefan; Katus, Hugo; Liebetrau, Christoph; Giannitsis, Evangelos; Searle, Julia (The American journal of medicine, 2016)
Background - The search for improved strategies for safe and early discharge of patients with suspected acute coronary syndrome in emergency departments is ongoing. This Biomarkers in Cardiology (BIC)-8 biomarker substudy evaluated the usefulness of high-sensitivity troponin T (hsTnT) below or above the limit of detection (LoD) in low-to-intermediate-risk patients with suspected acute coronary syndrome in the emergency department. - Methods - Patients were categorized into hsTnT ≥ the 99th percentile, between the 99th percentile and LoD, or undetectable hsTnT (<LoD). HsTnT and copeptin were measured at admission, using a copeptin cut-off of 10 pmol/L. The primary endpoint was death and myocardial infarction within 90 days after admission. - Results - Of 882 patients with all biomarker results, 577 (65.4%) had detectable hsTnT levels (≥LoD). Among the 305 patients (34.6%) with undetectable hsTnT, no myocardial infarctions or deaths occurred within 90 days. In patients with detectable hsTnT at admission (≥LoD but ≤99th percentile), the combined endpoint occurred in 1.5% (6/410) of the copeptin-negative patients and in 6.3% (6/96) of copeptin-positive patients within 90 days (hazard ratio 4.39; 95% confidence interval, 1.42-13.61; P = .01). In patients with an initially elevated hsTnT (≥14 ng/L), 9.7% (3/31) of the copeptin-negative patients and 15.4% (4/26) of the copeptin-positive patients experienced the combined endpoint (hazard ratio 1.61; 95% confidence interval, 0.36-7.17; P = .536). - Conclusions - In low-to-intermediate-risk patients with suspected acute coronary syndrome, undetectable hsTnT values at admission allow a safe discharge without occurrence of death or myocardial infarction within 90 days.
Gesehen am 29.05.2020